Beta-adrenergic- and muscarinic receptor-induced changes in cAMP activity in adult cardiac myocytes detected with FRET-based biosensor. - Warrier, S; Belevych, A; Ruse, M; Eckert, R; Zaccolo, M; Pozzan, T; Harvey, R (2005)
beta-Adrenergic receptor activation regulates cardiac myocyte function through the stimulation of cAMP production and subsequent activation of protein kinase A (PKA). Furthermore, muscarinic receptor activation inhibits as well as facilitates these cAMP-dependent effects. However, it has not always been possible to correlate the muscarinic responses with the direct measurement of changes in cellular cAMP activity. Genetically encoded biosensors have recently been developed, making it possible to monitor real-time changes in cAMP and PKA activity at the single cell level. One such biosensor consists of the regulatory and catalytic subunits of PKA labeled with cyan and yellow fluorescent proteins, respectively. Changes in cAMP activity affecting the association of these labeled PKA subunits can be detected as changes in fluorescence resonance energy transfer. In the present study, an adenovirus-based approach was developed to express this recombinant protein complex in adult cardiac myocytes and use it to monitor changes in cAMP activity produced by beta-adrenergic and muscarinic receptor activation. The biosensor expressed with the use of this system is able to detect changes in cAMP activity produced by physiologically relevant levels of beta-adrenergic receptor activation without disrupting normal functional responses. It was also possible to directly demonstrate the complex temporal pattern of inhibitory and stimulatory changes in cAMP activity produced by muscarinic receptor activation in these cells. The adenovirus-based approach we have developed should facilitate the use of this biosensor in studying cAMP and PKA-dependent signaling mechanisms in a wide variety of cell types.